Features of the Process of Professional Self-Determination in Children with Hearing Impairment - Krutsky, V.M.; Tikhomirov, M.Y. (Bulletin of Practical Psychology of Education, 2022)
This paper describes the results of a study of the process of professional self-determination of adolescents with hearing impairment. The authors dealing with this problem in the current century (Yu.S. Pyashkur, V.V. Tuarmensky and others) identified a number of features of the personal development of pupils of special educational institutions of adolescence and youth. Thus, communicative competence plays a significant role in the professional self-determination of adolescents with hearing impairments. The hypothesis about the special role of communicative competence in the process of professional self-determination of deaf adolescents was tested in the course of a study of students in a boarding school for children with hearing impairment aged 14–18 (N=23). The features of the professional inclinations of these students were revealed, a comparative analysis was carried out between the groups of adolescents and high school students. Based on the data obtained, a conclusion was made about the communicative orientation of activity as one of the most important targets for the professional self-determination of hearing-impaired adolescents. On the basis of the data obtained, a conclusion was made about the communicative competence of activity as one of the most important targets for professional self-determination of hearing-impaired adolescents. В данной работе описаны результаты исследования процесса профессионального самоопределения подростков с нарушением слуха. Авторы, занимающиеся данной проблемой в текущем веке (Ю.С. Пяшкур, В.В. Туарменский и др.), выделили ряд особенностей личностного развития воспитанников специальных учебных заведений подросткового и юношеского возраста. Так, значительную роль в профессиональном самоопределении подростков с нарушениями слуха играет коммуникативная компетентность. Гипотеза об особой роли коммуникативной компетентности в процессе профессионального само¬определения глухих подростков проверялась в ходе исследования учащихся школы-интерната для детей с нарушением слуха 14–18 лет (N=23). Выявлены особенности профессиональных склонностей данных учащихся, проведен сравнительный анализ между группами подростков и старшеклассников. На основе полученных данных сделан вывод о коммуникативной компетентности деятельности как одного из важнейших целевых ориентиров профессионального самоопределения слабослышащих подростков.